Hydrodynamic flow characteristics of tsunami waves impact on bearing wall layout. (December 2018) - Setyandito, Oki; Yuwono, Nur; Nizam,; Sjarifudin, Firza Utama; Mitchell,; Saragih, John Freddy Bobby
Abstract: Coastal zones management of a tsunami-prone area should be implemented with an effective and eco-friendly layout of near-shoreline structures. Eco-friendly layout term in this study means the layout produced a minimal bed scouring at the bottom of the structures. In this research, we studied the hydrodynamic flow caused by tsunami wave's propagation on the bearing walls in coastal area. This flow which occur in 2 (two) bearing wall layout variations were analysed using the Computational Fluid Dynamic (CFD) modelling program. The data and condition of the simulation are utilizing the bathymetric and topographic data of coastal area in the south of Yogyakarta, Java Island Indonesia. The simulation result shows that wave propagation reduction of square bearing wall 45° and 0° layout are 52, 99% and 59%, respectively. The square bearing wall 0° is not recommended to be applied due to its highest tsunami wave impact force on the wall structure. The square bearing wall of 0° has a higher shear force and lateral force. This forces can caused an unstable structure wall. The wave impact forces on wall structure area and layout is important parameter for changing the scouring parameter influenced.